2004
DOI: 10.1016/s0035-9203(03)00023-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopathy in complicated falciparum malaria: report from eastern India

Abstract: A prospective study done in 216 children with complicated falciparum malaria showed hepatopathy in 33.3% of cases with a higher incidence in children aged above five years. Bilirubin and alanine aminotransferase were moderately raised in most cases. No significant association with other common complications and no higher risk of mortality was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
2
5
0
1
Order By: Relevance
“…Prolonged APTT was seen in 82 cases with 25 cases of vivax, 52 cases of falciparum malaria and 5 cases of mixed infections. These findings from present study were comparable with findings of Jayshankar et al, Mohanthy et al 20,21 Severe thrombocytopenia (<50,000/mm 3 ) was observed in 100 cases (25%) with 25 cases in vivax, 64 cases of falciparum and 11 cases of mixed infections. These findings were comparable with findings of Shlee et al, Ghosh K et al 22,23 …”
Section: Laboratory Indicessupporting
confidence: 93%
“…Prolonged APTT was seen in 82 cases with 25 cases of vivax, 52 cases of falciparum malaria and 5 cases of mixed infections. These findings from present study were comparable with findings of Jayshankar et al, Mohanthy et al 20,21 Severe thrombocytopenia (<50,000/mm 3 ) was observed in 100 cases (25%) with 25 cases in vivax, 64 cases of falciparum and 11 cases of mixed infections. These findings were comparable with findings of Shlee et al, Ghosh K et al 22,23 …”
Section: Laboratory Indicessupporting
confidence: 93%
“…Out of 100 patients (35%) presented with severe malaria. This type of severe malaria was noted in other studies 15,16,17,18 . In our study maximum member of patients received atrisunate.…”
Section: Discussionsupporting
confidence: 82%
“…One could assume that liver manifestations would have been more acute provided the parasite life cycle had included a hepatocyte stage as in human malaria. Our finding of a hepatic encephalopathy is relevant to the understanding of the human disease, because hepatocellular dysfunction ranging from conjugated hyperbilirubinemia, with or without mild elevation in transaminases, to fulminant hepatic failure has been described in P. falciparum malaria (56,57). Therefore, subjects with malaria are at risk to develop a hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 83%